Hepatitis G virus in Saudi blood donors and chronic hepatitis B and C patients - Abdulkarim Alhetheel; Malak Mohsen El-Hazmi (Journal of Infection in Developing Countries)
Introduction: Screening blood donors for blood-borne pathogens is very critical for the recipient’s safety. Similar to hepatitis B and C infections, hepatitis G infection is transmitted through contaminated blood and causes acute and chronic hepatitis. Previous reports have shown that the prevalence of hepatitis G virus (HGV) RNA among healthy Saudi donors was 1%-2%. However, the exposure rate of this virus has never been studied. We hypothesized that the prevalence of HGV infection may have changed overtime due to socio-economic and environmental factors. Since hepatitis B and C infections are endemic in Saudi Arabia, we investigated the exposure rate of HGV infection in healthy donors and chronically infected hepatitis B and C patients. Methodology: A prospective study was done on healthy donors and patients with chronic HBV and HCV infections. Hepatitis B and C viral loads were measured by real-time polymerase chain reaction. HGV exposure rate was evaluated by detection of HGV antibodies. Results: Analysis of samples from healthy donors (n = 210), chronic HBV+ patients (n = 169), and chronic HCV+ patients (n = 105) showed that nine samples (4.3%), seven samples (4.1%), and four samples (3.8%) were positive for HGV antibodies, respectively. The non-significant difference in the exposure rates of HGV between the study groups may indicate that HGV infection occurs independent of HBV or HCV infections. Conclusions: We showed for the first time that the exposure rate of HGV infection among the Saudi population is 4.3%, and we recommend HGV screening for all blood donors.